2022
DOI: 10.1192/bjp.2022.2
|View full text |Cite
|
Sign up to set email alerts
|

Risk and resilience in trajectories of post-traumatic stress symptoms among first responders after the 2011 Great East Japan Earthquake: 7-year prospective cohort study

Abstract: Background First responders to disasters are at risk of developing post-traumatic stress disorder (PTSD). The trajectories of post-traumatic stress symptom severity differ among individuals, even if they are exposed to similar events. These trajectories have not yet been reported in non-Western first responders. Aims We aimed to explore post-traumatic stress symptom severity trajectories and their risk factors in first responders to the 2011 Great East Japan Earthquake (GEJE) – a histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In a 7-year prospective cohort study, five symptom severity trajectories were identified: resilient (54.7%), recovery (24.5%), incomplete recovery (10.7%), late-onset (5.7%), and chronic (4.3%). 51 In the overview above, several overlapping results have been reported regarding the longitudinal course of PTSD. This results in several perspectives.…”
Section: Chronological Course Of the Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…In a 7-year prospective cohort study, five symptom severity trajectories were identified: resilient (54.7%), recovery (24.5%), incomplete recovery (10.7%), late-onset (5.7%), and chronic (4.3%). 51 In the overview above, several overlapping results have been reported regarding the longitudinal course of PTSD. This results in several perspectives.…”
Section: Chronological Course Of the Disordermentioning
confidence: 99%
“…The largest study using LGMM identifying trajectories was performed on 56,388 first responders who were part of the Japan Ground Self‐Defense Force involved in the 2011 Great East Japan Earthquake. In a 7‐year prospective cohort study, five symptom severity trajectories were identified: resilient (54.7%), recovery (24.5%), incomplete recovery (10.7%), late‐onset (5.7%), and chronic (4.3%) 51 …”
Section: State‐of‐the‐artmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,9,10 Recent research has therefore focused on analyzing trajectories of PTSS after traumatic events. 11,12,13,14,15,16,17 Trajectories of PTSS are usually classified into four types: resilient, chronic, recovery, and delayed-onset. 11, 13, 14, 16 The resilient type shows stable low or no PTSD severity.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9,10 Recent research has therefore focused on analyzing trajectories of PTSS after traumatic events. 11,12,13,14,15,16,17 Trajectories of PTSS are usually classi ed into four types: resilient, chronic, recovery, and delayedonset. 11,13,14,16 The resilient type shows stable low or no PTSD severity.…”
Section: Introductionmentioning
confidence: 99%